2007
DOI: 10.1074/jbc.m609866200
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Initiation of Respiration and Mitochondrial Biogenesis in Rice

Abstract: Rice growth under aerobic and anaerobic conditions allowed aspects of mitochondrial biogenesis to be identified as dependent on or independent of an oxygen signal. Analysis of transcripts encoding mitochondrial components found that a subset of these genes respond to oxygen (defined as aerobic), whereas others are relatively unaffected by oxygen availability. Mitochondria formed during growth in anaerobic conditions had reduced protein levels of tricarboxylic acid cycle components and cytochrome-containing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 63 publications
2
86
0
Order By: Relevance
“…structural and functional development of mitochondria (Leaver and Lonsdale, 1989). Mitochondrial biogenesis during germination and early seedling growth has been studied in peanut (Morohashi et al, 1981), cucumber (Hill et al, 1992), maize (Ehrenshaft and Brambl, 1990;Li et al, 1996;Logan et al, 2001) and rice (Howell et al, 2006(Howell et al, , 2007. It has been reported that poorly differentiated but fully Edited by Toru Terachi * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…structural and functional development of mitochondria (Leaver and Lonsdale, 1989). Mitochondrial biogenesis during germination and early seedling growth has been studied in peanut (Morohashi et al, 1981), cucumber (Hill et al, 1992), maize (Ehrenshaft and Brambl, 1990;Li et al, 1996;Logan et al, 2001) and rice (Howell et al, 2006(Howell et al, , 2007. It has been reported that poorly differentiated but fully Edited by Toru Terachi * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Under 3-days high salinity stress even a greater increase occurred in the amount of cox2 transcript. Howell et al (2007) reported that cox2 was insensitive to oxygen until 12 h but then the level of its transcript increased by 3-fold under aerobic condition compared with anaerobic condition. Transcript level of the wheat AOX gene, Waox1a, showed a more than four-fold increase after 1-day low temperature stress as compared to the normal condition but it decreased after the 2nd day and remained unchanged until the 3rd day.…”
Section: Quantitative Real-time Rt-pcr Analysis Of Selected Mitochondmentioning
confidence: 99%
“…The extent of contribution of organellar gene expression in such stress response however remains largely unknown. A few studies have focused on mitochondrial gene expression, including ones in tobacco cultured cells during nutrient starvation (Giegé et al, 2005) and in rice plants germinating under low oxygen conditions (Howell et al, 2007). In rice, some mitochondrial components (cox2, cox5b-2, F 1 β-1, F 1 β-2) respond to low oxygen availability at both transcript and protein levels, while others like nad9 and cob remain unaffected (Howell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial function is required for the earliest steps of germination, both for ATP production and for its central role in a variety of metabolic processes (Law et al, 2014). Detailed analysis of mitochondrial respiration during germination in rice (Oryza sativa) revealed a biphasic increase in respiration rate, whereby oxygen uptake is detectable almost immediately on imbibition, which then stabilizes for some time before increasing greater than 4-fold (Howell et al, 2007a). The latter increase in respiration is accompanied by an increase in mitochondrial cristae structure and is accompanied by a temporal change in abundance for a variety of transcripts encoding components involved in mitochondrial biogenesis, which peak prior to transcripts and proteins encoding respiratory chain components (Howell et al, 2007b;Law et al, 2012).…”
mentioning
confidence: 99%